EMPLOYABILITY AND TRACER STUDY OF NURSING GRADUATES OF CENTRAL MINDANAO UNIVERSITY - Domagsang, Pilar Villahermosa; Camatura, Donald G.; M. Soliven, Dayanne Mae; D. Norh, Susan Beth (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Graduates of study programs at universities and colleges contribute significantly to the workforce, and their employability is crucial in both local and global labor markets. Understanding graduate employability and aligning academic preparation with industry needs are essential for improving educational outcomes, particularly in nursing education. Objective: This study aimed to determine the profile of nursing graduates, identify their employability status, and ascertain the employability attributes required by employers of nursing graduates from Central Mindanao University. Method: This study employed a descriptive research design conducted at Central Mindanao University using an online tracer study platform. The respondents included Bachelor of Science in Nursing (BSN) graduates and their respective employers, who were invited to complete structured survey questionnaires. The study traced graduates employed both locally and internationally. Results: Findings revealed that most graduates perceived the overall curriculum—including general education, core courses, electives, and undergraduate thesis—as highly useful for professional practice. The gap between employment and unemployment was largely attributed to graduates pursuing advanced studies or second degrees. Other contributing factors included family-related concerns, preparation for overseas employment, and review for licensure examinations such as NCLEX. Graduates identified key competencies gained from the program, ranked from most to least beneficial: work ethic, interpersonal skills, decision-making skills, teamwork, verbal communication, leadership, problem-solving, written communication, initiative, enthusiasm, and creativity. However, some graduates emphasized the need for increased practical training to enhance real-world readiness. From the employers' perspective, essential competencies to be strengthened in the BSN program include patient-centered care, evidence-based practice, interdisciplinary collaboration, quality improvement, and informatics utilization. Conclusion: The BSN curriculum at Central Mindanao University generally equips graduates with relevant competencies for professional practice. However, enhancing practical training and strengthening key employability skills aligned with employer expectations are necessary to further improve graduate readiness and competitiveness in the workforce.